The Use of Information and Communication Technology (ICT) in Early Childhood Learning Content in Laboratory Schools - IKA SUBEKTI; Lara Fridani; Nurjannah Nurjannah (Universitas Panca Sakti Bekasi, 2024)
This research aims to describe how ICT is applied in early childhood learning content in laboratory schools. Research focuses on the application of ICT to L-STEAM (Literacy, Science, Technology, Engineering, Art, Math) learning content. The research method used in this research is a case study. The research was conducted at one of the state university laboratory schools in Jakarta. Participants in this research were educators at laboratory schools called educarers. The research results show the use of ICT devices in the form of laptops, computers, tablets, smartphones, Android televisions and tape recorders in learning carried out in laboratory schools. More specifically, the research results also show the optimization of the use of ICT devices by educators to convey learning content in every activity carried out in laboratory schools. Educarer also expressed the importance of training to develop skills in the application of ICT to improve abilities in learning integrated with ICT. Apart from that, the educarer also conveyed the challenges faced in implementing ICT in laboratory schools.